Diseminasi Teknologi Pembuatan Sabun Padat Organik di SMPIT Raudhatul Ulum Desa Sakatiga Kabupaten Ogan Ilir: Dissemination of Organic Hard Soap Making Technology at SMPIT Raudhatul Ulum Sakatiga Village, Ogan Ilir Regency - Pratama, Filli; Syafutri, Merynda Indriyani; Defira, Citra; Lidiasari, Eka; Widowati, Tri Wardani; Syaiful, Friska; Sugito, Sugito; Tamrin, Tamrin; Pratiwi, Citra; Ichsan, Onne Akbar Nur (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
SMPIT Raudhatul Ulum is in Sakatiga Village, Ogan Ilir Regency, South Sumatra Province. One of the efforts to achieve the vision and mission, SMPIT Raudhatul Ulum collaborates with universities to improve and develop the quality of human resources, such as implementing community service activities related to the learning process. One of them is about the technology of making organic hard soap, which is part of chemistry learning. This community service activity aimed to provide knowledge, understanding, and training on the technology of making organic hard soap made from cucumber and coffee to teachers and students of SMPIT Raudhatul Ulum, Sakatiga Village, Ogan Ilir Regency. The method used was the lecture method, which was carried out through the delivery and explanation of material, accompanied by discussion, and the practice of making organic solid soap. The results showed that this activity could provide knowledge, understanding, and skills to the audience regarding organic hard soap made from cucumber and coffee powder, with an increase in the audience's understanding of organic hard soap of 26.02%, after the delivery of material and practice of making organic hard soap.